Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Exposure to O3, NO2 and their oxidative potential in relation to decreased fecundability: The potential contribution of inflammatory hematological markers - Bingxue Wu; Zigao Zhao; Yan Zhang; Cai Kong; Yuyan Li; Yishi Jiang; Zhengyuan Xie; Xiangjing Song; Tao Wang; Yan Che (Environmental Research, 2026)

A Positive Urbanization–Pollution–Fog Feedback Loop Revealed by High-Resolution Modeling over Eastern China - Duanyang Liu; Junlong Qian; Aichen Niu; Huizheng Che; Shuqi Yan; Ke Gui; Hongbin Wang; Zhujun Dai (Journal of Meteorological Research, 2026)

DMBT1 in Adipose-Derived Stem Cell-Derived Exosomes Participates in Alleviating Ferroptosis to Promote Diabetic Wound Healing - Yan Liu; Jinnan Wang; Yujiao Cai; Xiaoke Zhu; Zhanyuan Yuan; Jiahui Dai; Dehui Che; Dongsheng Cao (Stem Cell Reviews and Reports, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Mapping the comprehensive dataset of building-Level functional classifications in China - Yue Zheng; Xucai Zhang; Bin Chen; Geng Liu; Youli Zeng; Yan Yi; Jinpei Ou; Yangzi Che; Xiaoping Liu (Science Bulletin, 2026)

Vaginal Probiotic Potential of the Nomadic Species Limosilactobacacillus fermentum Under Dysbiotic Vaginal Conditions: Population Genomic Insights and Anti-Pathogenic Efficacy of a Vaginal Isolate VL9 - Yanqing Che; Yixin Mao; Mengjie Li; Xiao Liu; Hongzhou Li; Guodong Yan; He Gao; Xuemei Bai; Zhiwen Sun; Xiaoning Liu; Duochun Wang (Probiotics and Antimicrobial Proteins, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Fe-doped BiOBr nanosheets vertically grown on TiO2 nanotube arrays for photoelectrocatalytic treatment of reclaimed water - Gui Yang; Yu Yan; Xing Wan; Huan He; Jingxian Mei; Meina Zhu; Huachao Che; Junhui Zhang; Juhong Zhan; Xiaoyong Wu; Bin Huang; Xuejun Pan (Journal of Environmental Sciences, 2026)

Genome streamlining and functional adaptation of drought-enriched bacteria regulate soil heterotrophic respiration in alpine peatland - Yichang Gao; Yong Li; Zhongqing Yan; Kerou Zhang; Rongxiao Che; Lizhen Cui; Huan Wang; Yuechuan Niu; Enze Kang; Weirong Zhuang; Wenru Zhao; Miaomiao An; et al. (Plant and Soil, 2026)

Fungal co-cultivation reshapes salt stress adaptation in the cyanobacterium Synechococcus elongatus PCC 7942 - Ting Wang; Yuexuan Wang; Shujuan Wang; Yan Che; Tuanjie Che; Jie Feng; Tingting Li (Algal Research, 2026)

Evolution and Challenges of Marine Oil Spill Governance in Taiwan over Two Decades - Chih-Wei Chang; Shiau-Yun Lu; Chun-Pei Liao; Wen-Yan Chiau; Yi-Che Shih (Oceans, 2026)
Marine oil spills pose critical challenges to environmental sustainability and socioeconomic stability. Taking four pivotal cases as the entry point, this study uses comparative case analysis, semi-structured stakeholder interviews, policy analysis and international gap comparison to systematically analyze the evolution of marine oil spill governance in the Taiwan region of China over two decades, aiming to identify systemic gaps and propose actionable reforms. By integrating and explicitly detailing these multiple methodologies, this research not only identifies but also systematically examines the Taiwan region of China’s unique challenges as a non-UN-member entity navigating international conventions like the international convention for the prevention of pollution from ships, 1973, as modified by the protocol of 1978 relating thereto (MARPOL 73/78). Key findings reveal persistent issues in decision-support tools, fragmented inter-agency coordination, and legal inadequacies in compensation mechanisms. The study’s novelty lies in its rigorous synthesis of localized case-driven insights compared with global best practices, proposing a concrete, phased model for a unified task force and context-aware, data-driven contingency plans to enhance real-time response efficiency. It further advocates for pragmatic steps to align the Taiwan region of China’s Marine Pollution Control Act with international standards while critically addressing the transboundary collaboration barriers imposed by its political status, exploring potential pathways through sub-national and regional partnerships. Notably, the 2023 Angel Container case underscores the urgency of modernizing enforcement capacities and integrating advanced technologies. By bridging gaps in governance, legal accountability, and practical international engagement, this research not only advances the Taiwan region of China’s preparedness but also offers a nuanced and adaptable blueprint for coastal regions facing similar geopolitical and environmental constraints. Its recommendations hold significant implications for global marine pollution management, emphasizing the interplay of policy innovation, technological adoption, and pragmatic cross-jurisdictional cooperation.

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Partially etched Ti2AlN/Ti2N/TiN ternary composite as a synergistic catalyst for enhanced hydrogen storage kinetics and cycling stability of NaAlH4 - Chen Jin; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Lactobacillus Acidophilus Protects against alcohol-associated Liver Disease in Mice Via Gut Microbiota Modulation and Alleviation of Inflammation and Oxidative Stress - Jiaojiao Yang; Huan Yan; Jialu Liu; Xiaorong Shen; Haixia Liu; Xing Kang; Xiaodan Yang; Yuxin Che; Xiaohui Wang; Linzhi Guo; Fan zhang; Weiping Fan (Probiotics and Antimicrobial Proteins, 2026)

Hydrogeology of reservoirs for deep geological storage of saline coal mine drainage in groundwater Basin - Song Du; Zhan Yang; Xiao Zhang; Sheng Tao; Xiang Li; Qiaohui Che; Yinglin Fan; Yan Ding; Zhe Jiang; Yanxin Wang (Journal of Hydrology, 2026)

Joint inversion of hydraulic and thermal parameter fields using a CNN-based framework and transient hydraulic tomography - Che-Wei Liang; Jui-Pin Tsai; Zi-Yan Chou; Chia-Hao Chang; Bo-Tsen Wang (Journal of Hydrology, 2026)

Valorization of fly ash into hydrophobic mesoporous SiO₂ as a highly efficient and durable antifoaming agent for wet flue gas desulfurization - Fei Wang; Xiaoyan Yan; Xiaoke Li; Jiangtao Meng; Yu Che; Jing Wang; Yuanyuan Zhang (Journal of Environmental Chemical Engineering, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

A Self-adapting Polygenic Risk Score Model Improves Risk Prediction of Venous Thromboembolism in Han Chinese Cohorts - Yan Che (Phenomics, 2026)

The enhanced nitrous oxide emissions are driven by prokaryotic ammonia oxidizers and nirK-denitrifiers under various combinations of nitrogen and rice straw in a paddy soil - Chunyan Wu; Yinxiu Liu; Xu Tang; Tao Sun; Che Tan; Yu Zeng; Yan Li; Chang Yin; Yongchao Liang (Soil Ecology Letters, 2026)

Mechanistic insights into Ti3CN MXene-modified NaAlH4: Boosting hydrogen storage kinetics and cyclability - Chen Jin; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; Mi Yan (Chemical Engineering Journal, 2026)

Synergistic CeH2.51/graphene nanointerface engineering for enhanced kinetics and cycling stability of Mg(NH2)2–2LiH - Chen Jin; Haoyuan Zheng; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Low-temperature photothermal catalytic reforming: a promising approach for deep removal of biomass tar towards green fuels synthesis - Tianxiao Yu; Beibei Yan; Jian Li; Yuechi Che; Xiaopeng Jia; Guanyi Chen (Biomass and Bioenergy, 2026)

Robust Cu₂O-NiO-Pd interfaces enabling high-yield and long-term CO₂-to-CO conversion via reverse water-gas shift reaction - Amisha Beniwal; Wei-Hao Hsiung; Che Yan; Tsan-Yao Chen; Dinesh Bhalothia (Journal of Environmental Chemical Engineering, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Vegetation cover affects the response of greenhouse gas emissions to microplastics in a coastal wetland - Feifei Yan; Zihao Wang; Caijie Zhang; Ling Zhang; Zhikai Wang; Chunguang Che; Yuchi Xia; Jing Zhang (Water Research, 2026)

Molecular identification and characterization of a ‘Candidatus phytoplasma australasiaticum’ -related strain associated with Scaevola taccada virescence disease in China - Hai-Yan Che; Mei-Jiao Hu; Hai-Bo Long; Da-Quan Luo; Shao-Shuai Yu (Physiological and Molecular Plant Pathology, 2026)

Multi-proxy reconstruction of Holocene sedimentary evolution in the Yangtze Delta: Climatic forcing, sea-level oscillations, and diagenetic overprint - Zixuan Che; Chunzhu Chen; Lisi Wei; Wenwei Zhao; Quan Li; Yunpeng Yang; Hanfei Yang; Zhigang Wang; Xiaojian Zhang; Ximing Zhang; Shutong Yang; Huan Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

FeSe2 graphite intercalation compounds derived from spent graphite with spatial confinement effect enable high-performance sodium storage - Jiahao Yang; Chong Xu; Zizheng Zhou; Guang Ma; Shuang Liu; Dongyuan Zhang; Gong Cheng; Junjie Fu; Sai Che; Yan Jia; Yongfeng Li (Chemical Engineering Journal, 2026)

Hybrid nanozyme-natural enzyme catalytic system-based self-powered biosensing platform with dual-signal output for trace-level monitoring of pathogens - Bingtao Fu; Rongshuai Che; Haibo Wang; Yanni Luo; Defen Feng; Jiawen Wu; Jun Yan; Ke-Jing Huang; Xuecai Tan (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

From rolling-in to enveloping: An active gripper for efficient handling of spherical fruits in agriculture - Huanhuan Qin; Zicheng Qiu; Haoran Zhu; Rui Diao; Fengwei Che; Xingjian Gu; Yan Luo; Baohua Zhang; Mingzhou Lu (Computers and Electronics in Agriculture, 2025)

Volatilomic profiling of controlled atmosphere stored blue honeysuckle fruit using GC-MS, E-nose, and GC-IMS - Zhen Xiao; Qiuju Jing; Shuangyu Xie; Jinhui Sun; Jianing Che; Junwei Huo; Xiaonan Sui; Yaqi Lan; Yan Zhang (Postharvest Biology and Technology, 2025)

Identifying biomarkers for arsenic exposure-induced nonalcoholic fatty liver disease: An integrated proteomics, metabolomics, and machine learning approach - Yiqiong Sun; Fuping Li; Weizhen Hua; Zhenbin Che; Meiping Tian; Yan-Yang Lu; Qingyu Huang (Journal of Hazardous Materials, 2025)

Long-term substitution of chemical fertilizer with organic manure enhances the activity and autotrophic growth of ammonia-oxidizing archaea and comammox nitrospira in paddy soil - Chunyan Wu; Xu Tang; Che Tan; Tao Sun; Yu Zeng; Yinxiu Liu; Yingxia Liu; Yan Li; Yongchao Liang; Chang Yin (Journal of Environmental Management, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

Optimizing nitrogen form ratio for enhanced nutrient uptake and lettuce performance in hydroponic systems - Jing Xu; Gongye Che; Junqi Yan; Yun Luo; Allen Good; Tian Yuan; Zhongfang Lei; Zhenya Zhang; Kazuya Shizumi (Bioresource Technology Reports, 2025)

Study on Frost Deformation Characteristics of Transversely Isotropic Rocks Under Unidirectional Freeze–Thaw Cycles - Hanqing Lu; Weixing Bao; Yan Yin; Bowen Che; Zhenhua Pan (Rock Mechanics and Rock Engineering, 2025)

Diurnal Characteristics and Sources Apportionment of Atmospheric PM2.5 in a Medium-sized City in East China - Lingshuo Meng; Yang Du; Hanxiong Che; Jiawei Zhou; Zhier Bao; Yiliang Liu; Yan Han; Xin Qi; Sainan Wang; Xin Long; Yang Chen (Aerosol Science and Engineering, 2025)

Novel insight into the heavy metal immobilization by coal fly ash-based geopolymers using machine learning and density functional theory - Kaizhi Yang; Bo Yang; Kezhou Yan; Yining Su; Longyi Zhao; Jungang Tang; Yu Che; Yanxia Guo (Waste Management, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

Bioinspired multifunctional conductive hydrogel based on hydroxypropyl methyl cellulose for flexible sensors - Hongtian Yan; Haonan Gu; Shizhou Lu; Fanjun Meng; Qinglin Ma; Xiang Xing; Shihui Pan; Yuju Che (Carbohydrate Polymers, 2025)

Machine learning of lithium and gallium accumulation based on the major element contents in coal gangue from Shanxi province coalfields - Kezhou Yan; Longyi Zhao; Kaizhi Yang; Yu Che; Yanxia Guo; Fangqin Cheng (Applied Geochemistry, 2025)

A lightweight method for apple disease segmentation using multimodal transformer and sensor fusion - Yihong Song; Manzhou Li; Zizhe Zhou; Jiahe Zhang; Xiangge Du; Min Dong; Qinhong Jiang; Che Li; Yuantao Hu; Qiulin Yu; Dongmei Wang; Hegan Dong; et al. (Computers and Electronics in Agriculture, 2025)

Sodium silicate complex reduces subdermal hemorrhage and prolongs survival after envenomation by Trimeresurus stejnegeri stejnegeri - Yen-Chia Chen; Hao-Ming Chang; Chang-Chih Ke; Chia-Chun Liu; Yu-Kai Huang; Kun-Che Chang; Min-Hui Chen; Isaac Chun-Jen Chen; Yu-Wei Chiang; Po-Yu Liu; Chih-Sheng Lai; Kuo-Lung Lai; et al. (Toxicon, 2025)

Optimization of sandwich panels with multi-layer aluminium foam for explosion-prevention converter transformer turrets - Chenguang Yan; Yiyao Lyu; Qinzhi Liu; Ke Wang; Yikun Zhao; Jiaxu Guo; Hao Liu; Che Xu (Process Safety and Environmental Protection, 2025)

Role of lanthanum oxycarbonate in dendritic fibrous Ni/CHE-La catalyst on enhanced CO2 dissociation for low-temperature CO2 reforming of methane - Shi Yan Liew; Aishah Abdul Jalil; Tan Ji Siang; Fazilah Farhana Abdul Aziz; Anees Ameera Fauzi; Nurfatehah Wahyuny Che Jusoh; Lee Peng Teh; Saravanan Rajendran (Journal of Environmental Chemical Engineering, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Variation of flavor substance-producing microbiota in four seasons of Chinese liquor fermentation - Feng Liang; Zhiming Zhong; Shibo Ban; Ping Ma; Jing Hao; Jing Wu; Heqiang Huang; Fuhong Che; Qun Wu; Yan Xu (Systems Microbiology and Biomanufacturing, 2025)

Microbial interactions of floc and biofilm sludge in PN/A processes in anaerobic/aerobic/anoxic mode: Competition or cooperation? - Yan Zhang; Jiaao Wang; Meina Hu; Tao Ya; Che Liu; Lingzhi Feng; Xiaohui Wang (Journal of Water Process Engineering, 2025)

Perfluorooctane sulfonate exposure disrupts steroid hormone synthesis in rats via the gut-metabolism-testis axis - Weizhen Hua; Rui Yang; Md Nur Alam; Zhenbin Che; Wanqing Zhu; Meiping Tian; Yan-Yang Lu; Yan Sun; Qingyu Huang (Environmental Pollution, 2025)

Standard strategy for developing multicomponent nanopesticides: From gene function analysis to co-delivery nano-platform construction - Qinhong Jiang; Min Dong; Lin Che; Che Li; Xian Zhang; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Bi-layered cellulose-based aerogel with photothermal and photocatalytic dual functions for integrated solar-driven desalination and Cr(VI) reduction - Guodong Tian; Chao Duan; Shasha Che; Yan Li; Kang Yang; Jinyu Guo; Yuxin Zhou; Yijian Wen; Yonghao Ni (Chemical Engineering Journal, 2025)

Multi-biomimetic cellulose-based regenerated fibers from scalable wet spinning for ultrahigh-efficiency rate fog harvesting - Chao Duan; Yuanmei Liu; Jinyu Guo; Yan Li; Yijian Wen; Yiyang Che; Xiaoshuang Liu; Kang Yang; Yonghao Ni (Chemical Engineering Journal, 2025)

High-density magnetic-carbon interfaces in NiCu@C heterojunction toward broadband electromagnetic wave absorption - Zhikai Yan; Mengqiu Huang; Longjun Rao; Wenbin You; Biao Zhao; Lei Wang; Limin Wu; Ruixuan Zhang; Wei Li; Renchao Che (Chemical Engineering Journal, 2025)

Biopolymer-amended geosynthetic clay liners for landfills and contaminated sites: Gas and hydraulic performance - Ying-Zhen Li; Heng Zhuang; Ji-Ying Fan; Wei-Yi Xia; Jia-Lei Wan; Chi Che; Yan-Jun Du (Environmental Research, 2025)

SEBS-amended in-situ mixed wall material for diesel-contaminated groundwater management - Zhe-Yuan Jiang; Xian-Lei Fu; Fei Jin; Chi Che; Zhong-Yuan Li; Guojun Cai; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Dual-pathway photosynthesis H2O2 realized by carbon nitride with strong built-in electric field and awakened n-π* electron transition: Based on theoretical calculation guidance - Yuhan Yan; Tianyu Zhou; Chunbo Liu; Bo Hu; Guangbo Che (Chemical Engineering Journal, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Characterisation of greenhouse gas emissions from temporary wastewater treatment plants under different operation modes - Yan Yin; Weixing Bao; Bowen Che; Hanqing Lu; Xuhui Lin (Process Safety and Environmental Protection, 2025)

Association of ambient ozone with time to pregnancy and the modifying effect of ambient temperature: a population-based cohort study - Bingxue Wu; Tao Wang; Yan Zhang; Yuyan Li; Cai Kong; Yishi Jiang; Xiangjing Song; Xing Chen; Zhengyuan Xie; Hanfeng Ye; Lin Feng; Zigao Zhao; et al. (Environmental Pollution, 2025)

Synergy of single-atom iron and titanium-oxo cluster at oxygen vacancy in MIL-125-NH2 to achieve high-performance CO2-to-CH3OH photocatalysis - Yan Che; Changyan Zhu; Xin Liu; Mengying Li; Xingbing Liu; Hongzhu Xing (Chemical Engineering Journal, 2025)

Fault materials and creep characteristics in mudstone areas: A case study of Chegualin Fault in southwestern Taiwan - Pin-Hao Chen; Yen-Hua Chen; Ming-Chih Hsieh; Yan-Wei Huang; Chien-Che Huang; Wei-Teh Jiang; Jey-Jau Lee; Yao-Chang Lee; Hwo-Shuenn Sheu (Engineering Geology, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Synthesis of novel 18 β -glycyrrhetinic acid sulfonate derivatives displaying significant anti-oomycete activity against Phytophthora capsici - Yibo Liu; Yan Li; Yuee Tian; Yihao Guo; Ruxue Wei; Xiaobo Huang; Le Qian; Shengming Liu; Genqiang Chen; Zhiping Che (Natural Product Research, 2025)

Deciphering the microbiome, lipopolysaccharides, and metabolome interplay: Unveiling putrescine's mechanism for enhancing sperm quality in heat-stressed boars - Chenglong Yu; Hao Li; Lun Hua; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; De Wu; Junjie Zhang; Yan Lin (Theriogenology, 2025)

Bridging the gap between hyperspectral imaging and crop breeding: soybean yield prediction and lodging classification with prototype contrastive learning - Guangyao Sun; Yong Zhang; Lei Wang; Longyu Zhou; Shuaipeng Fei; Shiteng Han; Shunfu Xiao; Yingpu Che; Long Yan; Yun Xu; Yinghui Li; Lijuan Qiu; et al. (Computers and Electronics in Agriculture, 2025)

Association between ambient temperature and couple fecundity: Insights from a large-scale cohort study in Yunnan, China - Bingxue Wu; Tao Wang; Yan Zhang; Yuyan Li; Xing Chen; Zhengyuan Xie; Cai Kong; Yuzhi Lan; Hanfeng Ye; Xiangjing Song; Zigao Zhao; Yan Che (International Journal of Hygiene and Environmental Health, 2025)

Effects of forest fire on successional trajectory of understory vegetation in boreal permafrost region in Northeast China - Xiaoying Li; Hongwei Wang; Huijun Jin; Ruixia He; Xiaoying Jin; Yan Li; Gangyi Zhou; Fuqiang Che (Cold Regions Science and Technology, 2025)

Revealing the mechanisms of rhamnolipid enhancing methane production from anaerobic digestion of bituminous coal - Shufeng Zhao; Hongyu Guo; Norbert Klitzsch; Daping Xia; Xiao Liu; Yan Liu; Ying Che (Biomass and Bioenergy, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Epidemiology of liver diseases: global disease burden and forecasted research trends - Jia Xiao; Fei Wang; Yuan Yuan; Jinhang Gao; Lu Xiao; Chao Yan; Feifei Guo; Jiajun Zhong; Zhaodi Che; Wei Li; Tian Lan; Frank Tacke; et al. (Science China Life Sciences, 2025)

Segregation of sea breezes and cooling effects on land-surface temperatures in a coastal city - Lisu Chen; Yan Zhang; Enyan Zhu; Yue Che; Yueying Wu (Sustainable Cities and Society, 2025)

Establishment of genetic transformation system in Lilium pumilum and functional analysis of LpNAC6 on abiotic stress - Hongying Zhang; Hao Yan; Haitao Che; Kyongsok So; Longyi He; Yuxin Zhu; Bin Liu; Yanni Zhang (Plant Science, 2025)

Trifunctional surface engineering of Lithium-rich manganese-based oxides via Al3+/PO43− co-doping and oxygen vacancy regulation for High-performance lithium-ion batteries - Hongyun Zhang; Jinyang Dong; Gang Chen; Huiquan Che; Kang Yan; Xi Wang; Jinzhong Liu; Dewang Liu; Yun Lu; Ning Li; Yuefeng Su; Feng Wu; et al. (Chemical Engineering Journal, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Characteristics and health risks assessment of PM2.5-bound heavy metals during winter in urban areas of northern China: A case study in Kaifeng - Xin Qi; Yan Han; Hanxiong Che; Jiawei Zhou; Chao Peng; Zhier Bao; Yiliang Liu; Lingshuo Meng; Shumin Zhang; Fumo Yang; Wenbo Xue; Yu Lei; et al. (Science of The Total Environment, 2024)

Environmental changes and human impacts over the past 1200 years: Evidence from high-resolution pollen records from peat in the Yunnan-Guizhou Plateau, Southwest China - Shuming Li; Lisi Wei; Wenwei Zhao; Weihe Ren; Qinran Gu; Zixuan Che; Xianyong Cao; Huan Li; Xiaojian Zhang; Chunzhu Chen; Yan Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Identification of soybean mosaic virus strain SC7 resistance loci and candidate genes in soybean [Glycine max (L.) Merr.] - Yixiang Pu; Rujuan Yan; Dongbing Jia; Zhijun Che; Rufei Yang; Changyun Yang; Hui Wang; Hao Cheng; Deyue Yu (Molecular Genetics and Genomics, 2024)

The Multifaceted Roles of Hippo-YAP in Cardiovascular Diseases - Hao Wu; Yan-Nan Che; Qi Lan; Yi-Xiang He; Ping Liu; Ming-Tai Chen; Li Dong; Meng-Nan Liu (Cardiovascular Toxicology, 2024)

Design of a portable bioassay system based on highly efficent nanozyme and Au-DNA nanocluster: Toward current/colorimetric dual-signal detection of sugarcane smut - Danyao Tang; Zeping Wang; Rongshuai Che; Jie Liao; Meixin Yan; Xiaoqiu Zhang; Jun Yan; Ke-Jing Huang; Xuecai Tan; Yu Ya (Chemical Engineering Journal, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Determination of major drive of ozone formation and improvement of O3 prediction in typical North China Plain based on interpretable random forest model - Liyin Yao; Yan Han; Xin Qi; Dasheng Huang; Hanxiong Che; Xin Long; Yang Du; Lingshuo Meng; Xiaojiang Yao; Liuyi Zhang; Yang Chen (Science of The Total Environment, 2024)

Biogenic volatile organic compounds dominated the near-surface ozone generation in Sichuan Basin, China, during fall and wintertime - Dasheng Huang; Qing Li; Yan Han; Shi-Yong Xia; Jiawei Zhou; Hanxiong Che; Keding Lu; Fumo Yang; Xin Long; Yang Chen (Journal of Environmental Sciences, 2024)

Sediment resuspension as a driving force for organic carbon transference and rebalance in marginal seas - Xiaoqing Liu; Chunyuan Lan; Longhai Zhu; Caiqing Yan; Nan Wang; Haibiao Chen; Guangjin Zheng; Yangli Che; Zuosheng Yang; Rui Bao (Water Research, 2024)

Effect of storage on microbioa and enzyme proteomic profile of low-temperature Daqu - Feng Liang; Zhiming Zhong; Muyan Ma; Jing Hao; Ping Ma; Jing Wu; Heqiang Huang; Fuhong Che; Qun Wu; Yan Xu (Food Bioscience, 2024)

Multifunctional Spirulina-hybrid helical microswimmers: Imaging and photothermal efficacy enabled by intracellular gold deposition - Ziqiao Li; Yanan Che; Ming Chen; Jing Hu; Pan He; Xiang Sun; Xiaozhen Wu; Youliang Yao; Huili Zheng; Gang Liu; Xiaohui Yan (Chemical Engineering Journal, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Potential synergy between Pt2Ni4 Atomic-Clusters, oxygen vacancies and adjacent Pd nanoparticles outperforms commercial Pt nanocatalyst in alkaline fuel cells - Dinesh Bhalothia; Amisha Beniwal; Che Yan; Kai-Chin Wang; Chen-Hao Wang; Tsan-Yao Chen (Chemical Engineering Journal, 2024)

The mechanism of photothermal catalytic reforming of biomass tar: An exploratory study based on density functional theory - Beibei Yan; Tianxiao Yu; Jian Li; Xiaopeng Jia; Zhiyu Li; Yuechi Che; Guanyi Chen; Juan Zhao (Fuel, 2024)

Concentration-dependent alterations in the human plasma proteome following controlled exposure to diesel exhaust - Juma Orach; Mahadevappa Hemshekhar; Christopher Francis Rider; Victor Spicer; Amy H. Lee; Agnes Che Yan Yuen; Neeloffer Mookherjee; Chris Carlsten (Environmental Pollution, 2024)

Pricing, greening, and recycling decisions of capital-constrained closed-loop supply chain with government subsidies under financing strategies - Jianhui Chen; Yan Tian; Felix T.S. Chan; Huajun Tang; Pak Hou Che (Journal of Cleaner Production, 2024)

Projections of Greenland climate change from CMIP5 and CMIP6 - Qinglin Zhang; Baojuan Huai; Minghu Ding; Weijun Sun; Weigang Liu; Jinpei Yan; Shuhui Zhao; Yetang Wang; Yuzhe Wang; Lei Wang; Jiahang Che; Jiahui Dou; et al. (Global and Planetary Change, 2024)

Migration and adsorption of naphthalene in road-deposited sediments from stormwater runoff: Impact of the particle size - Hongze Liu; Fuguo Qiu; Mingchen Gao; Yongjian Che; Chaohong Tan; Ziyang Zhang; Rui Yan; Haiyan Li; Meipeng Jian (Science of The Total Environment, 2023)

From cellulose to tar: Analysis of tar formation pathway with distinguishing the primary and secondary reactions - Xiaopeng Jia; Yuechi Che; Jian Li; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Juan Zhao (Bioresource Technology, 2023)

Study on the Mechanism of Eerdun Wurile’s Effects on Post-operative Cognitive Dysfunction by the TLR4/NF-κB Pathway - Yun Qiao; Huiru Li; Yan Li; Enboer Su; Zhe Wang; Limuge Che; Yiri Du (Molecular Neurobiology, 2023)
The object of our work was to observe whether the Mongolian medicine Eerdun Wurile (EW) improve postoperative cognitive dysfunction (POCD) by affecting the TLR4/NF-κB. Mice (6–8-week-old male C57BL/6 J) were selected to establish an animal model of POCD by combining intracerebroventricular injection of lipopolysaccharide and nephrectomy; EW formulation and EW basic formulation were administered intra-gastrically for 7 consecutive days. The cognitive performance was assessed by Morris water maze test. H&E staining was examined to detect alterations in hippocampal tissue. Immunohistochemical staining was performed to evaluate MyD88, NF-κB, TLR4, iNOS, and IBA-1 expressions; Western blotting and RT-qPCR were performed to evaluate MyD88, NF-κB, and TLR4. The expressions of IL-6, IL-1β, and TNF-α were evaluated by ELISA. Intracerebroventricular injection of lipopolysaccharide combined with nephrectomy induced cognitive dysfunction in mice, stimulated TLR4/NF-κB and microglia, and promoted the secretion of murine TNF-α, IL-1β, and IL-6. EW formulation and EW basic formulation treatment are able to suppress the TLR4/NF-κB pathway activation and microglia, and the serum cytokine secretions related to proinflammation, and restore the cognitive performance. EW formulation and EW basic formulation can improve POCD in mice, and TLR4/NF-κB pathway seems to be one of the important mechanisms in EW’s improvement of POCD.

Experimental study on multi-scale damage and deterioration mechanism of carbonaceous slate under freeze-thaw cycles - Hanqing Lu; Weixing Bao; Yan Yin; Xun Sun; Huizhou Li; Zhenhua Pan; Bowen Che (Bulletin of Engineering Geology and the Environment, 2023)

In situ growth of polydopamine modified ZIF-L arrays on air-laid paper as flexible evaporator for efficient solar desalination - Long Cheng; Linzhi Zuo; Shitan Yan; Jiubing Shen; Chengping Li; Yiting Che; Liang Wang; Romanov Anton; Ting Bian (Desalination, 2023)

Toxicity evaluation of silica nanoparticles for delivery applications - Yue Tan; Dawei Yu; Jiayao Feng; Huimin You; Yan Bai; Jincan He; Hua Cao; Qishi Che; Jiao Guo; Zhengquan Su (Drug Delivery and Translational Research, 2023)

High-entropy transition metal disulfide colloid clusters: synergistic atomic scale interaction and interconnected network for ultra-stable potassium ion storage - Yan-Jie Liao; Wei-Wen Shen; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Springtime reactive volatile organic compounds (VOCs) and impacts on ozone in urban areas of Yunnan-Guizhou plateau, China: A PTR-TOF-MS study - Qing Li; Yan Han; Dasheng Huang; Jiawei Zhou; Hanxiong Che; Liuyi Zhang; Keding Lu; Fumo Yang; Yang Chen (Atmospheric Environment, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

A novel magnetic buoyant-bead flotation method for the removal of typical microalgae from harmful algal blooms - Yan Zhao; Xuexue Wu; Wenjuan Chang; Wenlu Che; Yi Liu; Yanpeng Li (Journal of Environmental Chemical Engineering, 2023)

Sequential exposures of single walled carbon nanotubes and heavy metal ions to macrophages induce different cytotoxicity - Long Kong; Guizhen Yan; Xinxin Huang; Yanxin Wu; Xin Che; Jian Liu; Jianbo Jia; Hongyu Zhou; Bing Yan (Science of The Total Environment, 2023)

Effects of Organic Chromium Yeast on Performance, Meat Quality, and Serum Parameters of Grow-Finish Pigs - Yunhan Liu; Bin Huo; Zhongping Chen; Kun Wang; Lingjie Huang; Lianqiang Che; Bin Feng; Yan Lin; Shengyu Xu; Yong Zhuo; Caimei Wu; De Wu; et al. (Biological Trace Element Research, 2023)

Ultra-trace detection and efficient adsorption removal of multiple water-soluble volatile organic compounds by fluorescent sensor array - Huachao Che; Shulin Yan; Ming Xiong; Yulun Nie; Xike Tian; Yong Li (Journal of Hazardous Materials, 2023)

Oxygen vacancies endow atomic cobalt-palladium oxide clusters with outstanding oxygen reduction reaction activity - Thomas Yang; Dinesh Bhalothia; Hong-Wei Chang; Che Yan; Amisha Beniwal; You-Xun Chang; Shun-Chi Wu; Po-Chun Chen; Kuan-Wen Wang; Sheng Dai; Tsan-Yao Chen (Chemical Engineering Journal, 2023)

Novel applications of vacuum distillation for heavy metals removal from wastewater, copper nitrate hydroxide recovery, and copper sulfide impregnated activated carbon synthesis for gaseous mercury adsorption - Che-Jung Hsu; Yan-Ze Xiao; Adrienne Chung; Hsing-Cheng Hsi (Science of The Total Environment, 2023)

Effects of Toxin-Antitoxin System HicAB on Biofilm Formation by Extraintestinal Pathogenic E. coli - Bo Hou; Chen-Yan Wang; Shao-Wen Li; Lun-Jiang Zhou; Yong-Liang Che; Qiu-Yong Chen (Current Microbiology, 2023)

Response of bacterial communities in saline-alkali soil to different pesticide stresses - Juan Che; Yan Lei Zhu; Yan Hong Li; Rui Zhang; Zhi Yong Ruan; Wei Zhang (Environmental Science and Pollution Research, 2022)

Effect of strontium on nutrient uptake, physiological parameters, and strontium localization in lettuce - Dong Yan; Kuke Ding; Yingxue He; Li Fan; Yongfei Che; Yingjun Zhao; Xiaoyan Jiang (Environmental Science and Pollution Research, 2022)

Notch activation suppresses endothelial cell migration and sprouting via miR-223-3p targeting Fbxw7 - Ruonan Wang; Ziyan Yang; Liang Liang; Xingxing Feng; Bo Che; Xiaoyan Zhang; Qijun Zheng; Xianchun Yan; Hua Han (In Vitro Cellular & Developmental Biology - Animal, 2022)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

Comprehensive Management of Rural Water Pollution in Polder Wetland: a Case Study of the Chenhai Wei Polder Wetland in the Taihu Basin of China - Lubing Yan; Changkun Xie; Anze Liang; Ruiyuan Jiang; Shengquan Che (Wetlands, 2021)

Changes in the Microbiome of the Inner Surface of Clear Aligners After Different Usage Periods - Dong Yan; Yi Liu; Xiaoxia Che; Sicong Mi; Yao Jiao; Lijia Guo; Song Li (Current Microbiology, 2021)

Multifunctional Microparticles Incorporating Gold Compound Inhibit Human Lung Cancer Xenograft - Pui -Yan Lee; Chun-Nam Lok; Chi-Ming Che; Weiyuan John Kao (Pharmaceutical Research, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Biochar shifts biomass and element allocation of legume-grass mixtures in Cd-contaminated soils - Yan Xiao; Leqi Wang; Zhuojun Zhao; Yeye Che (Environmental Science and Pollution Research, 2020)

Malus niedzwetzkyana (Dieck) Langenf transcriptome comparison and phylogenetic analysis with Malus sieversii (Ledeb) Roem - Meiling Yang; Shiyou Che; Yunxiu Zhang; Wenqin Song; Guorong Yan; Weiwei Yu (Genetic Resources and Crop Evolution, 2020)

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

The High-Frequency Decay Parameter (Kappa) in Taiwan - Shun-Chiang Chang; Kuo-Liang Wen; Ming-Wey Huang; Chun-Hsiang Kuo; Che-Min Lin; Chun-Te Chen; Jyun-Yan Huang (Pure and Applied Geophysics, 2019)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Increased N fertilizer input enhances CH4 and N2O emissions from soil amended with low amount of milk vetch residues - Xiao Sun; Yeye Che; Yan Xiao (Paddy and Water Environment, 2019)

Construction of rGO wrapping Cu2O/ZnO heterostructure photocatalyst for PNP and PAM degradation - Fang Liu; Yangli Che; Qingwen Chai; Mengfei Zhao; Yan Lv; Hui Sun; Yongqiang Wang; Juan Sun; Chaocheng Zhao (Environmental Science and Pollution Research, 2019)

Application of double-yield model in numerical simulation of stability of mining filling body - Bingqian Yan; Saijie Che; Dwayne D. Tannant; Fenhua Ren; Peitao Wang (Arabian Journal of Geosciences, 2019)

Effects of rice straw incorporation and N fertilizer on ryegrass yield, soil quality, and greenhouse gas emissions from paddy soil - Fengge Zhang; Yeye Che; Yan Xiao (Journal of Soils and Sediments, 2019)

Antibacterial and anticorrosive properties of CuZnO@RGO waterborne polyurethane coating in circulating cooling water - Guofei Jiang; Xufei Li; Yangli Che; Yan Lv; Fang Liu; Yongqiang Wang; Chaocheng Zhao; Xiaojuan Wang (Environmental Science and Pollution Research, 2019)

Interferon-γ regulates cell malignant growth via the c-Abl/HDAC2 signaling pathway in mammary epithelial cells - Wen-bo Ren; Xiao-jing Xia; Jing Huang; Wen-fei Guo; Yan-yi Che; Ting-hao Huang; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2019)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

First report of tobacco mosaic virus infecting Benincasa hispida in Jiangxi Province in China - Feng Zhu; Yang Kai Zhou; Ya Qian Zhao; Yan Ping Che; Zhao Lin Ji (Journal of Plant Pathology, 2018)

First report of cucumber mosaic virus infecting Arachis hypogaea in Jiangxi Province in China - Feng Zhu; Yan Ping Che; Yang Kai Zhou; Shi Chang Cheng; Zheng Liu; Zhao Lin Ji (Journal of Plant Pathology, 2018)

High-resolution characterization of arsenic mobility and its correlation to labile iron and manganese in sediments of a shallow eutrophic lake in China - Changzhou Yan; Liqing Zeng; Feifei Che; Fan Yang; Dapeng Wang; Zhuanxi Luo; Zaosheng Wang; Xinhong Wang (Journal of Soils and Sediments, 2018)

Effects of different fertilizers on growth and nutrient uptake of Lolium multiflorum grown in Cd-contaminated soils - Mohan Liu; Yang Li; Yeye Che; Shaojun Deng; Yan Xiao (Environmental Science and Pollution Research, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Variability of Antarctic Intermediate Water south of Australia and its relationship with frontal waves - LinLin Zhang; XiaoMei Yan; Che Sun; DunXin Hu (Science China Earth Sciences, 2016)

Transcriptome sequencing and de novo analysis of Rosa multiflora under cold stress - Xiaoying Zhang; Jinzhu Zhang; Weiwei Zhang; Tao Yang; Yan Xiong; Daidi Che (Acta Physiologiae Plantarum, 2016)

Feasibility of A-mode ultrasound attenuation as a monitoring method of local hyperthermia treatment - Noraida Abd Manaf; Maizatul Nadwa Che Aziz; Dzulfadhli Saffuan Ridzuan; Maheza Irna Mohamad Salim; Asnida Abd Wahab; Khin Wee Lai; Yan Chai Hum (Medical & Biological Engineering & Computing, 2016)

Molecular phylogeography of white‐lipped tree viper ( Trimeresurus ; Viperidae) - Fei Zhu; Qin Liu; Jing Che; Liang Zhang; Xin Chen; Fang Yan; Robert Murphy; Cong Guo; Peng Guo (Zoologica Scripta, 2016)
The white‐lipped tree viper ( Trimeresurus albolabris ) is one of the most common venomous snakes with medicine importance in South East Asia. To explore the genetic diversity, population structure and evolutionary history of Trimeresurus albolabris, we collected 98 samples from 27 localities covering its entire distribution. Two mitochondrial gene fragments (cyt‐b and ND‐4) and two nuclear genes (RAG‐1 and NT‐3) were sequenced and analysed. Bayesian inference and maximum‐likelihood methods were employed to reconstruct the phylogenetic relationships among populations based on the two mitochondrial fragments, and the median‐joining networks were depicted using nuclear genes. Divergence date and ancestral area were estimated, and the population demographic history was inferred. Both phylogenetic analyses consistently uncovered that Trimeresurus albolabris was monophyletics, with five geographically structured lineages. Divergence date and ancestral area estimation indicated that T. albolabris originated in northern Thailand and eastern Myanmar at c . 7.15 Ma. Population dynamics analyses showed the southern China lineage has experienced population expansion and contraction, but the others have not. Both the interglacial expansion and the highly heterogeneous habitats resulting from the uplift of the Plateau played a joint role in shaping the present distribution and population structure. The evolutionary history of T. albolabris can be explained by a pattern of two direction dispersal: first from North to South, and then from West to East.

Serum Uric Acid Levels and Diabetic Peripheral Neuropathy in Type 2 Diabetes: a Systematic Review and Meta-analysis - Shuai Yu; Ying Chen; Xu Hou; Donghua Xu; Kui Che; Changgui Li; Shengli Yan; Yangang Wang; Bin Wang (Molecular Neurobiology, 2016)

Element distribution over the surface of fish scales and its connection to the geochemical environment of habitats: a potential biogeochemical tag - TsingHai Wang; Yan-Chen Lai; Chia-Che Chiang; Yu-Rong Cheng; Yi-Kong Hsieh; Chu-Fang Wang (Environmental Monitoring and Assessment, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Multilevel analysis of a riverscape under rapid urbanization in the Yangtze delta plain, China: 1965–2006 - Huifeng Zhu; Xiangyu Ren; Yan Jin; Kai Yang; Yue Che (Environmental Monitoring and Assessment, 2015)

The associations between metals/metalloids concentrations in blood plasma of Hong Kong residents and their seafood diet, smoking habit, body mass index and age - Yan Yan Qin; Clement Kai Man Leung; Che Kit Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

A QTL with major effect on reducing leaf rust severity on the short arm of chromosome 1A of wheat detected across different genetic backgrounds and diverse environments - Ziyi Du; Mingzhe Che; Guohui Li; Jiang Chen; Wei Quan; Yan Guo; Zhen Wang; Junda Ren; Huyan Zhang; Zhongjun Zhang (Theoretical and Applied Genetics, 2015)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Oxidative stress, apoptosis, and cell cycle arrest are induced in primary fetal alveolar type II epithelial cells exposed to fine particulate matter from cooking oil fumes - Ying Liu; Yan-Yan Chen; Ji-Yu Cao; Fang-Biao Tao; Xiao-Xia Zhu; Ci-Jiang Yao; Dao-Jun Chen; Zhen Che; Qi-Hong Zhao; Long-Ping Wen (Environmental Science and Pollution Research, 2015)

An altimetric transport index for Kuroshio inflow northeast of Taiwan Island - XiaoMei Yan; Che Sun (Science China Earth Sciences, 2015)

Preparation and application of collagen scaffold-encapsulated silver nanoparticles and bone morphogenetic protein 2 for enhancing the repair of infected bone - Chang-ying Sun; Yan-jun Che; Shi-jin Lu (Biotechnology Letters, 2015)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Nutrient restriction induces failure of reproductive function and molecular changes in hypothalamus–pituitary–gonadal axis in postpubertal gilts - Dongsheng Zhou; Yong zhuo; Lianqiang Che; Yan Lin; Zhengfeng Fang; De Wu (Molecular Biology Reports, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Residents’ concerns and attitudes toward a municipal solid waste landfill: integrating a questionnaire survey and GIS techniques - Yue Che; Kai Yang; Yan Jin; Weiqian Zhang; Zhaoyi Shang; Jun Tai (Environmental Monitoring and Assessment, 2013)

Mapping of QTL conferring resistance to sharp eyespot (Rhizoctonia cerealis) in bread wheat at the adult plant growth stage - Jiang Chen; Guo Hui Li; Zi Yi Du; Wei Quan; Hu Yan Zhang; Ming Zhe Che; Zhen Wang; Zhong Jun Zhang (Theoretical and Applied Genetics, 2013)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

Investigation of EEG abnormalities in the early stage of Parkinson’s disease - Chun-Xiao Han; Jiang Wang; Guo-Sheng Yi; Yan-Qiu Che (Cognitive Neurodynamics, 2013)

Statin use and risk of bladder cancer: a meta-analysis - Xiao-long Zhang; Jiang Geng; Xiao-peng Zhang; Bo Peng; Jian-ping Che; Yang Yan; Guang-chun Wang; Sheng-qiang Xia; Yan Wu; Jun-hua Zheng (Cancer Causes & Control, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)

Syntheses of novel diaryl[d,f ][1,3]diazepines via one-pot Suzuki coupling followed by direct ring closure with carboxylic acids - Longjia Yan; Xin Che; Xu Bai; Yazhong Pei (Molecular Diversity, 2012)

Synthesis of benzopyrano[4,3-b](N-arylsulfonyl)indoles and benzopyrano[3,4-b](N-arylsulfonyl)indoles via intramolecular palladium-catalyzed aryl–aryl coupling reaction - Ling-ling Fan; Zhi-ping Che; Rui Zhang; Xiang Yu; Xiao-yan Zhi; Hui Xu (Molecular Diversity, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

A disease associated with phytoplasma in Parthenium hysterophorus - Zhengnan Li; Lei Zhang; Haiyan Che; Hongguang Liu; Ming Chi; Daquan Luo; Yan Li; Wang Chen; Yunfeng Wu (Phytoparasitica, 2011)

A NMR-based metabolomic approach for differentiation of hagfish dental and somatic skeletal muscles - Kuo-Hsun Chiu; Shangwu Ding; Yan-Wen Chen; Che-Hsin Lee; Hin-Kiu Mok (Fish Physiology and Biochemistry, 2011)

Effect of 1-methylcyclopropene on postharvest physiological changes of ‘Zaohong’ plum - Juan Kan; Jing Che; Hai Yan Xie; Chang Hai Jin (Acta Physiologiae Plantarum, 2011)

CCK mediated the inhibitory effect of oxytocin on the contraction of longitudinal muscle strips of duodenum in male rats - Yinglian Lv; Mei Feng; Tongtong Che; Hui Sun; Yan Luo; Kejing Liu; Chuanyong Liu (Pflügers Archiv - European Journal of Physiology, 2010)

Postnatal expression and denervation induced up-regulation of aquaporin-5 protein in rat sweat gland - Lei Ma; Yuan-Gui Huang; Hua He; Yan-Chun Deng; Hai-Feng Zhang; Hong-Lei Che; Ji-Yu Tian; Gang Zhao (Cell and Tissue Research, 2007)

Factors of influence on microbial pollution in the atmosphere over Beijing area - Che Fengxiang; Hu Qingxuang; Chen Zhensheng; Meng Lingyin; Yan Shigang (Aerobiologia, 1991)